Establishing diagnostic criteria and treatment of subsegmental pulmonary embolism: A Delphi analysis of experts. Issue 8 (1st October 2020) - den Exter, Paul L.; Kroft, Lucia J. M.; Gonsalves, Carol; Le Gal, Gregoire; Schaefer‐Prokop, Cornelia M.; Carrier, Marc; Huisman, Menno V.; Klok, Frederikus A.
Abstract: Background: Improved imaging techniques have increased the incidence of subsegmental pulmonary embolism (ssPE). Indirect evidence is suggesting that ssPE may represent a more benign presentation of venous thromboembolism not necessarily requiring anticoagulant treatment. However, correctly diagnosing ssPE is challenging with reported low interobserver agreement, partly due to the lack of widely accepted diagnostic criteria. Objectives: We sought to derive uniform diagnostic criteria for ssPE, guided by expert consensus. Methods: Based on an extensive literature review and expert opinion of a Delphi steering committee, two surveys including statements regarding diagnostic criteria and management options for ssPE were established. These surveys were conducted electronically among two panels, respectively: expert thoracic radiologists and clinical venous thromboembolism specialists. The Delphi method was used to achieve consensus after multiple survey rounds. Consensus was defined as a level of agreement >70%. Results: Twenty‐nine of 40 invited radiologists (73%) and 40 of 51 clinicians (78%) participated. Following two survey rounds by the expert radiologists, consensus was achieved on 15 of 16 statements, including on the established diagnostic criteria for ssPE (96% agreement): a contrast defect in a subsegmental artery, that is, the first arterial branch division of any segmental artery independent of artery diameter, visible in at least two subsequent axial slices, using a computed tomography scanner with a desired maximum collimator width of ≤1 mm. These criteria were approved by 83% of the clinical venous thromboembolism (VTE) specialists. The clinical expert panel favored anticoagulant treatment in case of prior VTE, antiphospholipid syndrome, pregnancy, cancer, and proximal deep vein thrombosis. Conclusion: The results of this analysis provide standard radiological criteria for ssPE that may be applicable in both clinical trials and practice.